The Meaning of Communication in Fashion Style of Muslim Student in Institut Agama Islam (IAI) Al-Aziziyah Samalanga Bireuen Aceh - Saiful Bahri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Changes in Muslim fashion trends will not be dammed and will continue to experience changes. Different from the previous year, where the trend of Muslim clothing in Indonesia tends to show an experimental trend. This year, the experimental trend has shifted to a long head covering known as the hijab syar’i. The term shari'i used, refers to Muslim women's clothing where the clothes, according to the Islamic Shari'ah guidance. Therefore, many call this ongoing fashion trend with shar'i hijab. Moving on from that thought, the problem to be investigated in this research is the meaning of Muslimah fashion communication style for Al-Aziziyah Samalanga Bireuen Aceh's Islamic Religion Institute (IAI) students. To uncover the problem thoroughly and deeply, this study uses a qualitative descriptive method that is useful for providing data and facts about the meaning of communication in the style of Al-Aziziyah Samalanga Islamic Institute (IAI) student dress style. Then the data were analyzed with the basis of the thought of George Herbert Mead and the principle of George Ritzer, in order to obtain a deep meaning about the student's fashion style. Meaning is produced from religious background, motives, and social environment. After that, meaning is modified through an interpretive process, and then individuals develop self-concepts through interactions with others. Self-concept provides an important motive for behavior and expression in choosing a style of dress. From the results of the study it was found that the meaning of communication style of Muslim female students of the Islamic Religious Institute (IAI) Al-Aziziyah Samalanga was produced from a background of religiosity, motives, and social environment. Then, individuals do the process of self-communication and produce a meaning that is interpreted through clothing. Some of the meanings of communication of Muslim female student fashion styles The Islamic Religious Institute (IAI) Al-Aziziyah Samalanga are produced based on the female Muslim students' fashion styles, namely: The meaning of Muslimah women's fashion styles as self-identities, the meaning of Muslimah women's fashion styles as a lifestyle, and the meaning of Muslim women's clothing styles as a form of obedience. Fashion communication is produced through the use of various symbols and fashion styles, so that the attitudes and behaviors of the user are reflected and generate direct appreciation through the interaction of people around. Several ways of meaning female students of communication style of Islamic clothing Islamic Institute of Islam (IAI) Al-Aziziyah Samalanga communicates Muslim clothing styles: Dressing in one color from top to bottom, fashion that is in accordance with Islamic law and ignores the trend of the times, follows the trend of Muslim fashion at the time that, dress in colors, mix and match the color of clothing.